2018
DOI: 10.1038/s41416-018-0212-9
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of circulating tumour DNA is associated with inferior outcomes in Ewing sarcoma and osteosarcoma: a report from the Children’s Oncology Group

Abstract: NGS assays agnostic of primary tumour sequencing results detect ctDNA in half of the plasma samples from patients with newly diagnosed EWS and osteosarcoma. Detectable ctDNA is associated with inferior outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 36 publications
5
114
0
Order By: Relevance
“…72,82,91,92 NGS assays have also been utilized to detect variants associated with a worse outcome, including TP53 mutations and STAG2 loss in Ewing sarcoma, 8q gain in osteosarcoma, MYCN amplification in neuroblastoma, 1q gain in Wilms tumor, and PAX3 gene rearrangements in alveolar rhabdomyosarcoma. 82,83 Although prior studies identified known prognostic genetic features in ctDNA, we demonstrated that detection of ctDNA itself provided prognostic information at diagnosis in patients with Ewing sarcoma and osteosarcoma. 83 Using a hybrid-capture NGS assay, ctDNA could be detected in over half of patients with Ewing sarcoma from a cooperative group biobank of plasma samples.…”
Section: First Authormentioning
confidence: 71%
See 4 more Smart Citations
“…72,82,91,92 NGS assays have also been utilized to detect variants associated with a worse outcome, including TP53 mutations and STAG2 loss in Ewing sarcoma, 8q gain in osteosarcoma, MYCN amplification in neuroblastoma, 1q gain in Wilms tumor, and PAX3 gene rearrangements in alveolar rhabdomyosarcoma. 82,83 Although prior studies identified known prognostic genetic features in ctDNA, we demonstrated that detection of ctDNA itself provided prognostic information at diagnosis in patients with Ewing sarcoma and osteosarcoma. 83 Using a hybrid-capture NGS assay, ctDNA could be detected in over half of patients with Ewing sarcoma from a cooperative group biobank of plasma samples.…”
Section: First Authormentioning
confidence: 71%
“…Adalsteinsson et al showed that ctDNA can be quantified by measuring genome‐wide segmental copy‐number changes from ultralow‐passage WGS (ULP‐WGS) using the ichorCNA algorithm . We recently applied this approach to the most common non‐CNS pediatric solid tumors, and we demonstrated that the majority of pediatric malignant tumors shed ctDNA at detectable levels . One advantage of this approach is that quantification of ctDNA does not require prior tumor profiling or the need for a germline sample.…”
Section: Detection Quantification and Characterization Of Ctdna In mentioning
confidence: 98%
See 3 more Smart Citations